A Study of Key Management for Encrypted Storage in Storage Area Network - Hai Xin LU (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics, 2009)
As secure storage becomes more pervasive throughout the enterprise,the focus quickly moves from implementing encrypting storage devices toestablishing effective and secure key management policies. Without the properkey generation, distribution, storage, and recovery, valuable data will beeventually compromised [9]. Although a considerable amount of research hasbeen dedicated to encryption algorithms in the past decades, key managementbecomes an issue due to the quantity of data. For example, with millions of datayou will need million set of keys. To manage and keep track of these keys,complexity and operational inefficiency becomes an issue. How to manage keysbecomes a challenging task. Adequate understanding of these new challenges isessential to effectively devise new key management policies and mechanisms toguard against them. We discuss many of these methods in this new context tofill this gap